2019
DOI: 10.3390/jcm8091310
|View full text |Cite
|
Sign up to set email alerts
|

A Lesion-Based Convolutional Neural Network Improves Endoscopic Detection and Depth Prediction of Early Gastric Cancer

Abstract: In early gastric cancer (EGC), tumor invasion depth is an important factor for determining the treatment method. However, as endoscopic ultrasonography has limitations when measuring the exact depth in a clinical setting as endoscopists often depend on gross findings and personal experience. The present study aimed to develop a model optimized for EGC detection and depth prediction, and we investigated factors affecting artificial intelligence (AI) diagnosis. We employed a visual geometry group(VGG)-16 model f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(113 citation statements)
references
References 25 publications
1
104
0
Order By: Relevance
“…Transfer learning for low-level CNN features from various non-medical source tasks using deep CNN representations showed good performance for the automatic detection and classification of colorectal polyps. 44,46,47 The proposed diagnostic model, which minimized the time-consuming pre-processing, outperformed the previous state-of-the-art methods.…”
Section: Ai-based Classification In Endoscopymentioning
confidence: 94%
“…Transfer learning for low-level CNN features from various non-medical source tasks using deep CNN representations showed good performance for the automatic detection and classification of colorectal polyps. 44,46,47 The proposed diagnostic model, which minimized the time-consuming pre-processing, outperformed the previous state-of-the-art methods.…”
Section: Ai-based Classification In Endoscopymentioning
confidence: 94%
“…Yoon et al named this process, "lesion-based CNN". 36 They reported that it showed better performance than other CNNs in the detection of EGC and depth prediction. The Grad-CAM loss was applied to the existing cross-entropy loss to reduce localization errors.…”
Section: Lesion-based Convolutional Neural Networkmentioning
confidence: 99%
“…Smart AI‐assisted systems integrating detection and diagnosis will become a new focus of research . Mori et al worked on an automated colonoscopic observation that is hoped to be able to detect and characterize diminutive polyps simultaneously.…”
Section: Current Situation Of Ai‐aided Endoscopic Image Recognitionmentioning
confidence: 99%
“…As assistant observers or clinical decision‐makers, AI‐aided systems undoubtedly have a promising future in increasing the effective training of junior endoscopists . Furthermore, it has emerged that, given the advantages of computer vision, the depth of tumor invasion can be predicted …”
Section: Future Challenges Of Ai In Gi Endoscopymentioning
confidence: 99%
See 1 more Smart Citation